HUKUM-HUKUM PERTUMBUHAN DAN PERKEMBANGAN: HUKUM-HUKUM PERTUMBUHAN DAN PERKEMBANGAN - rahmatia inaku; Evandri Paputungan; Frezy paputungan (Jurnal Ilmu Pendidikan dan Budaya, 2023)
Growth is a process of increasing height, volume or body mass in living things. This process is quantitative or can be measured and calculated with numbers. Development is a process towards maturity with changes in thoughts, emotions and skills that are more mature. Growth and development are natural phenomena that occur in all living things, including humans. These laws are the principles governing the processes of growth and development that have had a significant impact on biology, psychology, and economics. Piaget's Laws of Development describe the stages of cognitive development that children go through as they get older. Growth and development are complex processes in human life, and an understanding of these laws is important for understanding and supporting healthy development. There are several well-known laws of human growth and development, including the laws of physical growth, the laws of cognitive development, and the laws of social and emotional development. These laws cover general patterns that occur throughout life, such as physical growth, the development of thinking, learning, and understanding information, and the social and emotional development of relationships with other people. Understanding the laws of growth and development is valuable insight into our understanding of growth and development processes. This knowledge plays an important role in various aspects of life, from education, health, to making economic decisions.